Mechanical properties and simulation of finite element firmness in Carica papaya L. Tainung F1 cultivated on the high Sinu (Cordoba-Colombia) - Arrázola, Guillermo; Villadiego, Fernando; Alvis, Armando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The objective of this research was to evaluate Tainung F1 papaya fruits in five degrees of ripeness, analyzing mechanical resistance and modeling behavior with finite element analysis to generate important postharvest and transport management data. Tainung F1 papaya fruits were evaluated in five degrees of ripeness by analyzing their mechanical strength. Firmness was determined by applying a uniaxial penetration test and mechanical properties with an axial compression test. The firmness modeling and simulation was done with Autodesk inventor professional 15.0 (ANSYS® Technology). The deformability modulus decreased with the increase in the degree of ripeness, from 1.81 MPa to 0.52 MPa for degree of ripeness 1 to degree of ripeness 5. The yield strength varied from 0.0073 MPa to 0.00239 MPa for the same range. The finite element simulation of the fruit firmness showed a negative correlation with the degree of ripeness.